Overdominant expression of genes plays a key role in root growth of tobacco hybrids - Pi, Kai; Huang, Ying; Luo, Wen; Zeng, Shuaibo; Mo, Zejun; Duan, Lili; Liu, Renxiang (Frontiers in Plant Science, 2023)
Heterosis has greatly improved the yield and quality of crops. However, previous studies often focused on improving the yield and quality of the shoot system, while research on the root system was neglected. We determined the root numbers of 12 F1 hybrids, all of which showed strong heterosis, indicating that tobacco F1 hybrids have general heterosis. To understand its molecular mechanism, we selected two hybrids with strong heterosis, GJ (G70 × Jiucaiping No.2) and KJ (K326 × Jiucaiping No.2), and their parents for transcriptome analysis. There were 84.22% and 90.25% of the differentially expressed genes were overdominantly expressed. The enrichment analysis of these overdominantly expressed genes showed that "Plant hormone signal transduction", "Phenylpropanoid biosynthesis", "MAPK signaling pathway - plant", and "Starch and sucrose metabolism" pathways were associated with root development. We focused on the analysis of the biosynthetic pathways of auxin(AUX), cytokinins(CTK), abscisic acid(ABA), ethylene(ET), and salicylic acid(SA), suggesting that overdominant expression of these hormone signaling pathway genes may enhance root development in hybrids. In addition, Nitab4.5_0011528g0020、Nitab4.5_0003282g0020、Nitab4.5_0004384g0070 may be genes involved in root growth. Genome-wide comparative transcriptome analysis enhanced our understanding of the regulatory network of tobacco root development and provided new ideas for studying the molecular mechanisms of tobacco root development.